2021
DOI: 10.3390/ijerph18158010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salivary miRNAs That Predict Chronic Periodontitis Progression: A Cohort Study

Abstract: The aim of this two-year cohort study was to investigate salivary microRNAs (miRNAs) that predict periodontitis progression. A total of 120 patients who underwent supportive periodontal therapy were recruited. Unstimulated whole saliva was collected at baseline. Two years later, 44 patients were followed up (median age, 67.1 years) and divided into two groups: progression group (n = 22), with one or more sites with clinical attachment level (CAL) progression (>3 mm compared with baseline) or tooth extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…found that miR-28-5p was dramatically downregulated in CP. 11 Furthermore, miR-28-5p plays a critical function in the inflammatory response to disease. miR-28-5p was identified as a strongly upregulated miRNA in patients with axial spondylolisthesis 9 but it was downregulated in the inflammation of colon cancer caused by Fusobacterium nucleatum , and its levels were significantly negatively correlated with the inflammatory factor IL-6 in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that miR-28-5p was dramatically downregulated in CP. 11 Furthermore, miR-28-5p plays a critical function in the inflammatory response to disease. miR-28-5p was identified as a strongly upregulated miRNA in patients with axial spondylolisthesis 9 but it was downregulated in the inflammation of colon cancer caused by Fusobacterium nucleatum , and its levels were significantly negatively correlated with the inflammatory factor IL-6 in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…analyzed miRNAs associated with the progression of chronic CP by microarray, in which miR-28-5p expression was greatly suppressed. 11 However, the specific role of miR-28-5p in CP is unknown. Gingival crevicular fluid (GCF) is a fluid secreted by the gingival sulcus of teeth, which can be used to monitor the development of CP to adopt a targeted treatment plan, and a large number of miRNAs in GCF are identified and can modulate the CP immune response, 12 for example, miR-140-3p, miR-145-5p and miR-195-5p.…”
Section: Introductionmentioning
confidence: 99%
“…In microarray analysis of patients with CP, salivary hsa-miR-5571-5p, hsa-let-7f-5p, hsa-miR-99a-5p, hsa-miR-28-5p, and hsa-miR-320d expression was linked to periodontitis development. These salivary miRNAs could be novel biomarkers for periodontitis progression and monitoring them could lead to new periodontal diagnostics and precision therapy ( Fujimori et al, 2021 ).…”
Section: Salivary Exosome In Periodontitismentioning
confidence: 99%
“…Therefore, they suggested that these miRNAs may act as a predictive biomarker for periodontal disease progression. Furthermore, bioinformatics analysis indicated that these miRNAs are involved in periodontal pathology, through the regulation of the MAPK signaling pathway (Fujimori et al, 2021). The pathway is involved in tissue inflammation and cell death by inducing apoptosis (Kumar et al, 2021).…”
Section: Salivary Exosomal Mirnas In Patients With Periodontitismentioning
confidence: 99%
“…The pathway is involved in tissue inflammation and cell death by inducing apoptosis (Kumar et al, 2021). Moreover, the upregulation of miR‐99a‐5p induces leukocyte migration, resulting in exacerbating inflammation (Fujimori et al, 2021).…”
Section: Salivary Exosomal Mirnas In Patients With Periodontitismentioning
confidence: 99%